The Application Domain Extension (ADE) 4D Cadastral Data Model and Its Application in Turkey - Surmeneli, Hicret Gursoy; Koeva, Mila; Alkan, Mehmet (MDPI, 2022)
The 3D cadastre, one of the most fundamental components of the 3D LAS (Land Administration System), aims to provide an integrated 3D view of legal (Right, Restrictions, and Responsibilities-RRR) and physical boundaries in multi-storey properties; therefore, to extend the flexible and modular basis of LADM, which best represents legal boundaries and RRRs, some integrated models using technical standards (e.g., CityGML, IFC, InfraGML) are developed to represent the full 3D cadastre. However, since most of the developed 3D integrated data models are designed at the conceptual level, there is a knowledge gap in logical data model relationships, which is the next processing step in the fully integrated 3D data model stage. The main argument of this study is an innovative ADE 4D Cadastral Data Model to represent 3D cadastral objects registration with time attributes using LADM and CityGML. The data management and organization are done in an open-source database for the Turkish cadastral system. This research will discuss two main topics. The first is how to implement a suitable way of realising LADM-based 3D cadastral object registration by focusing on developing the presentation of those cadastral objects to 4D (3D + t), with time attributes in alignment with the jurisdictional framework in Turkey. The second is how the data is managed in an open-source PostgreSQL database. In addition, the usage type of cadastral objects is shown in a CesiumJS, a visualisation platform. Moreover, this study will contribute to eliminating the knowledge gap between the conceptual and logical models.
Keywords: 3D-4D cadastre; LADM; CityGML; 3D database management system; PostgreSQL; 3D visualizations; 3D; LEGAL; Environmental Sciences & Ecology